Related Factor of Fertile Age Couples (PUS)’ s Participation in Family Planning Program - Imel Lodo; Yoseph Kenjam; Dominirsep O. Dodo (Universitas Nusa Cendana, 2023)
Population problems in Indonesia are large population numbers, high population growth, uneven population distribution, and low quality of life Government efforts to control population growth. A family planning program is issued to create a quality and prosperous family with a controlled birth rate. This study aims to analyze factors related to the participation of couples of childbearing age in family planning programs for people with low incomes in the work area of the Delha health center by 2021. The type of research used observational analysis with a cross-sectional study design. The population of all couples of childbearing age of people with low incomes is 1.049 people. The sampling technique uses simple random sampling with a sample of 80 people. The data obtained were analyzed using a meaningful rate of α = 0.05. The results showed that the five research variables studied had a relationship with pus participation in the birth control program. The p-value of each variable is as follows: Family Hope Program Assistance (95% CI = 2,362 to 50,794; p=0,002), Family Income (95% CI = 0.018 to 0.630; p=0.004), Number of children (95% CI = 0.009 to 0.980; p=0.002), Access to Contraceptive Services (95% CI = 1,779 to 35,620; p=0.008), Husband Support (95% CI = 0.063 to 0.925; p=0.000). Therefore, couples of childbearing age are expected to follow a family planning program.